Validation of four Malaxis species (Orchidaceae) - Dressler, Robert L. (Lankesteriana: International Journal on Orchidology, 2016)
Names of four species of Malaxis, described as new without a Latin diagnosis in Selbyana 24(2), 2003, are validated here.